Serologic evidence for selected infectious diseases in Marsican brown bears (Ursus arctos marsicanus) in Italy (2004-09). - DI FRANCESCO, Cristina Esmeralda; MARSILIO, Fulvio; Gentile L; Di Pirro V; Ladiana L; Tagliabue S (Journal of Wildlife Diseases, 2015)
We tested 30 serum samples collected during 2004-09 from 22 free-ranging Marsican brown bears (Ursus arctos marsicanus) in the National Park of Abruzzo, Lazio, and Molise, Italy, for antibodies against canine distemper virus (CDV), canine adenovirus type 2 (CAV-2), canine parvovirus type 2 (CPV-2), Brucella spp., and eight Leptospira interrogans sensu lato serovars. Antibody to CDV was detected in 11 samples (37%); only two bears (10%) had detectable CAV-2 and Brucella spp. antibodies; three bears were positive for L. interrogans serovar Bratislava; and one sample had antibody against L. interrogans serovar Copenhageni. All samples were positive for CPV-2 antibody. The CPV-2 antibody titers varied from 1∶640 to 1∶10,240, suggesting that transmission was still active. Fifty percent of bears were positive for antibody to two or more pathogens. Our results highlight the need to consider infectious diseases as a potential risk for Marsican brown bear conservation.